Petrology and 40Ar-39Ar age of the bimodal Orduzu volcanics (Malatya) from the western end of the eastern Anatolian Neogene volcanism, Turkey - Onal, Ayten; Boztug, Durmus; Arslan, Mehmet; Spell, Terry L.; Kurum, Sevcan (Tubitak Scientific & Technological Research Council Turkey, 2008)
The Orduzu volcanics, which are part of the Yamadag volcanics in the Malatya region, include rhyolite, rhyolitic dykes, trachyandesite and basaltic trachyanclesitic dykes. Mafic globular occurrences within the basaltic trachyandesitic dykes, the existence of basaltic trachyandesite enclaves within the trachyandesite, and other textural and geochemical evidence all indicate magma mingling/mixing. Incremental 40Ar-39Ar dating on plagioclase from the rhyolite, from rhyolite dykes and basaltic trachyandesite yielded consistently 16 Ma (Middle Miocene). Primordial mantle-normalized spider diagrams of the rhyolite and rhyolitic dykes represent enrichments in some large ion lithophile elements (Cs, Rb, Ba, K, Th, U) but remarkably depletion in Sr, Nb, Ti, Eu and slight depletion in some high field strength elements (Hf, Zr) relative to the trachyandesites and basaltic trachyanclesitic dykes. Chondrite-normalized rare earth element spidergrams yield a high (La/Lu)(CN) (18-47) and Eu/Eu* (0.57-0.92) ratios for the rhyolites and rhyloitic dykes, but a low (La/Lu)(CN) (7-13) and Eu/Eu* (0.86-1.05) values for the trachyandesites and basaltic trachyandesitic dykes. From the field relations and geochemical data, it is concluded that three distinct magma sources were spatially and temporally involved in the genesis of the Orduzu volcanics, that include a calc-alkaline, crustal-derived rhyolitic melt, another calc-alkaline, lithospheric mantle-derived andesitic magma, and a mildly alkaline, lithospheric mantle-derived basaltic magma.
Keywords: petrology; Ar-Ar dating; Neogene volcanism; Malatya; eastern Anatolia; Turkey